ISHELL: a 1–5 micron R = 80, 000 Immersion Grating Spectrograph for the NASA Infrared Telescope Facility. (11th January 2022) - Rayner, John; Tokunaga, Alan; Jaffe, Daniel; Bond, Timothy; Bonnet, Morgan; Ching, Gregory; Connelley, Michael; Cushing, Michael; Kokubun, Daniel; Lockhart, Charles; Vacca, William; Warmbier, Eric
Abstract: iSHELL is a 1.06–5.3 μ m high spectral resolution spectrograph built for the 3.2 m NASA Infrared Telescope Facility (IRTF) on Maunakea, Hawaii. Dispersion is accomplished with a silicon immersion grating in order to keep the instrument small enough to be mounted at the Cassegrain focus of the telescope. The white pupil spectrograph produces resolving powers of up to about R ≡ λ / δλ = 80, 000 (0.″375 slit). Cross-dispersing gratings mounted in a tiltable mechanism allow observers to select different wavelength ranges and, in combination with a slit wheel and Dekker mechanism, slit widths ranging from 0.″375 to 4.″0 and slit lengths ranging from 5″ to 25″. One Teledyne 2048 × 2048 HAWAII-2RG array is used in the spectrograph, and one Raytheon 512 × 512 Aladdin 2 array is used in a 1–5 μ m slit viewer for object acquisition, guiding, and scientific imaging. iSHELL has been in productive regular use on IRTF since first light in 2016 September. In this paper we discuss details of the science case, design, construction and astronomical use of iSHELL.